2014
DOI: 10.1038/nature13902
|View full text |Cite|
|
Sign up to set email alerts
|

In vivo engineering of oncogenic chromosomal rearrangements with the CRISPR/Cas9 system

Abstract: Chromosomal rearrangements play a central role in the pathogenesis of human cancers and often result in the expression of therapeutically actionable gene fusions1. A recently discovered example is a fusion between the Echinoderm Microtubule-associated Protein-like 4 (EML4) and the Anaplastic Lymphoma Kinase (ALK) genes, generated by an inversion on the short arm of chromosome 2: inv(2)(p21p23). The EML4-ALK oncogene is detected in a subset of human non-small cell lung cancers (NSCLC)2 and is clinically relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
513
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 586 publications
(534 citation statements)
references
References 30 publications
13
513
0
8
Order By: Relevance
“…One potential limitation of multiplexed CRISPR/Cas9 mutagenesis is that, in principle, combinatorial sgRNA targeting could lead to undesired large chromosomal rearrangements (18,20). To examine this possibility, we performed PCR-based screening for all possible deletions at chromosomes that were targeted by multiple sgRNAs (SI Appendix, Fig.…”
Section: Chromosomal Rearrangements Induced By Combinatorial Crispr/cas9mentioning
confidence: 99%
See 1 more Smart Citation
“…One potential limitation of multiplexed CRISPR/Cas9 mutagenesis is that, in principle, combinatorial sgRNA targeting could lead to undesired large chromosomal rearrangements (18,20). To examine this possibility, we performed PCR-based screening for all possible deletions at chromosomes that were targeted by multiple sgRNAs (SI Appendix, Fig.…”
Section: Chromosomal Rearrangements Induced By Combinatorial Crispr/cas9mentioning
confidence: 99%
“…This break is repaired by nonhomologous end joining, which commonly leaves a short insertion or deletion (indel), allowing homozygous disruption of the targeted gene. Recent studies showed that CRISPR/Cas9 is functional in germ cells and somatic cells of mice and can be used for gene editing and cancer induction in the lung and the biliary compartment (14)(15)(16)(17)(18)(19)(20). Targeting of Pten and p53 in the liver was reported to induce Significance Assigning biological relevance and molecular function to large catalogues of mutated genes in cancer is a major challenge.…”
mentioning
confidence: 99%
“…Her worries began at a meeting in 2014, when she saw a postdoc present work in which a virus was engineered to carry the CRISPR components into mice. The mice breathed in the virus, allowing the CRISPR system to engineer mutations and create a model for human lung cancer 4 . Doudna got a chill; a minor mistake in the design of the guide RNA could result in a CRISPR that worked in human lungs as well.…”
Section: Research Revolutionmentioning
confidence: 99%
“…Beaucoup moins vont audelà pour analyser les conséquences biologiques des modifications introduites. Parmi les réalisations les plus significatives dans le domaine biomédical voici quelques exemples spectaculaires donnés dans l'ordre chronologique : -2014 : obtention de réarrangements chromosomiques reproduisant des situations observées en oncologie 23 ; -2015 : élaboration de la méthode MCR (Mutagenic Chain Reaction) où une modification hétéro-zygote agit en trans de manière autocatalytique pour obtenir l'homozygotie en court-circuitant la transmission mendélienne 24 . Ce procédé d'abord validé chez la Drosophile a été appliqué chez l'Anophèle vecteur de l'agent du paludisme.…”
Section: Pas De Crispation Terminologique Autour Du Terme « éDition »unclassified